DIAGNOSIS AND MANAGEMENT OF THALASEMIC CARDIOMYOPATHY - AGUNG RIZKA PRATAMA (Jurnal Kedokteran Syiah Kuala, 2021)
Thalassemia is a autosomal recessive inherited conditions characterized by decreased or absent polypeptide chain synthesis resulting in reduced hemoglobin in red blood cells and anemia. Synthesis disorders are characterized by ineffective formation of erythropoiesis which causes the need for lifelong transfusions, this will lead to increased intestinal iron absorption and leading to iron accumulation in vital organs, accumulation of iron in the heart can cause myocardial dysfunction including serious complications such as cardiomipopathy of the heart, where thalassemic cardiomyopathy is a the main cause of morbidity was 63.6% and the main cause of death was 71% of thalassemia patients. It is necessary to early detection for thalassemia cardiomyopathy, such as periodic electrocardiography and echocardiography examinations to assess diastolic and systolic functions so that they do not develop into cardiomyopathy. The proper management of heart failure due to thalassemia cardiomyopathy must be optimally given to patients including chelation therapy which can be used as cardioprotective in thalassemic patients.